Mutation status of skeletal muscle contractile genes (tnnt3 and tpm2) among malay clubfoot patients: determination using pcr-dna sequencing analysis - Ariff, Mohamad Faris Md (2022)
Introduction Clubfoot or congenital talipes equinovarus (CTEV) is one of the most common congenital musculoskeletal anomalies and the incidence of 1 in 1000 births. Idiopathic and non-idiopathic clubfeet demonstrate calf muscle hypoplasia at birth which remains small even after corrective treatment of the clubfoot. We conducted this study to look for any skeletal gene mutations in idiopathic CTEV, as it is well described in non-idiopathic CTEV. Methodology This study was carried out in 33 idiopathic CTEV children that get their treatment in Hospital Universiti Sains Malaysia. Buccal swab was obtained from the child and the sample was sent to Human Genome Centre, Universiti Sains Malaysia (USM). DNA was extracted and purity was quantified. PCR was conducted in optimum condition and followed by agarose gel electrophoresis. DNA sequencing done and any mutations were observed and recorded. The results for DNA sequencing was analyzed statistically. Result In our study, no mutations detected in all the study participants for TPM2: c.308A>G and TNNT3: c.187C>A. Therefore, the association between the TPM2: c.308A>G and TNNT3: c.187C>A gene mutations and the clubfoot severity in Malay patients with idiopathic clubfoot was undetermined. No statistical analysis was conducted since the outcome of the dependent variable (TPM2: c.308A>G and TNNT3: c.187C>A mutations) was constant (no mutation). Conclusion No mutation was found in TPM2 and TNNT3 gene, hence the association with the clubfoot severity is undetermined. However, we cannot totally exclude the skeletal muscle genes as here are few more genes that are responsible for development and function of skeletal muscle.